TINGKAT KECEMASAN IBU HAMIL TRIMESTER III DALAM MENGHADAPI PERSALINAN PERTAMA - Rostina Afrida Pohan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
The first pregnancy for a woman is one of the crisis periods in her life, peace of mind is important in facing childbirth, because it is recommended not only to do physical exercises but also psychological exercises to deal with childbirth. The type of research used in this research is descriptive with a cross sectional approach. This design was carried out on a set of objects that were studied to reduce the level of anxiety of pregnant women facing the first delivery, with a total sample of 20 pregnant women. The data collected in this study were analyzed using tabulating. Of the 20 respondents studied, 2 people (10%) experienced mild anxiety, 12 people (60%) experienced moderate anxiety, and 5 people (25%) experienced severe anxiety and only 1 person 5% of respondents did not experience anxiety. The results of this study indicate the level of anxiety of pregnant women has been described in this study. In connection with this research, it is suggested to health workers and midwives who assist in childbirth to provide regular counseling to pregnant women about pregnancy and the delivery process.